Learning from automatically labeled data: case study on click fraud prediction. Issue 2 (February 2016) - Berrar, Daniel
Abstract In the era of big data, both class labels and covariates may result from proprietary algorithms orground models . The predictions of these ground models, however, are not the same as the unknownground truth . Thus, the automatically generated class labels are inherently uncertain, making subsequent supervised learning from such data a challenging task. Fine-tuning a new classifier could mean that, at the extreme, this new classifier will try to replicate the decision heuristics of the ground model. However, few new insights can be expected from a model that tries to merely emulate another one. Here, we study this problem in the context of click fraud prediction from highly skewed data that were automatically labeled by a proprietary detection algorithm. We propose a new approach to generate click profiles for publishers of online advertisements. In a blinded test, our ensemble of random forests achieved an average precision of only 36.2 %, meaning that our predictions do not agree very well with those of the ground model. We tried to elucidate this discrepancy and made several interesting observations. Our results suggest that supervised learning from automatically labeled data should be complemented by an interpretation of conflicting predictions between the new classifier and the ground model. If the ground truth is not known, then elucidating such disagreements might be more relevant than improving the performance of the new classifier.